Servol pre-school and adolescent training programmes in Trinidad and Tobago - Mahabir-Wyatt, Diana (UNESCO, 1993)
This document describes the preschool and adolescent training programmes of Servol. Servol provides preschool teacher training, curriculum development, supervision of classroom management, assistance with furniture and facilities, and ongoing teacher development for some 154 preschools in Trinidad and Tobago. It also provides teacher training, curricula, and supervision for 41 Adolescent Life Centres. The document outlines the nature and objectives of the programmes, examines the extent and management of the collaboration with the Ministry of Education, discusses the educational and institutional achievements, and provides some recommendations for the future.
Keywords: Servol